Diet and weigh disorders (Journal of Parents and Teachers, 2013)
The authors let us know the progressive increasing of the problems related to the feeding behavior, weigh, and body image. They also explain some alimentary disorders, overweigh and obesity and analyze the influence of the media and internet in these problems.
Keywords: Feeding; obesity; anorexia; media; Family and guidance; education.